2008
DOI: 10.1095/biolreprod.108.067595
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Androgens on Serum Concentrations of Gonadotropins and Ovarian Steroids in Gilts1

Abstract: To examine how androgens affect endocrine events associated with increased ovulation rate, gilts were injected with androgen receptor agonists, an antagonist, or a combination of both. Blood samples were collected hourly from Day 13 to estrus (Day 0 = onset of estrus) coincident with gilts (n = 6 per treatment) receiving daily treatments of vehicle (corn oil), 10 mg of testosterone, 10 mg of 5 alpha-dihydrotestosterone (dihydrotestosterone), 1.5 g of flutamide (an androgen receptor antagonist), testosterone pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…The P4 production in small and large luteal porcine cells is stimulated by luteinizing hormone (LH). 52 Jimenez et al 53 demonstrated that the LH level is significantly decreased following the administration of testosterone or dihydrotestosterone plus flutamide in gilts. An indirect action of androgens via changes in LH rather than a direct effect may be responsible for the observed changes in the GD90F large luteal cells.…”
Section: Effect Of Flutamide On Cyp11a1 Luteal Expressionmentioning
confidence: 99%
“…The P4 production in small and large luteal porcine cells is stimulated by luteinizing hormone (LH). 52 Jimenez et al 53 demonstrated that the LH level is significantly decreased following the administration of testosterone or dihydrotestosterone plus flutamide in gilts. An indirect action of androgens via changes in LH rather than a direct effect may be responsible for the observed changes in the GD90F large luteal cells.…”
Section: Effect Of Flutamide On Cyp11a1 Luteal Expressionmentioning
confidence: 99%
“…Figure 1 shows the process of paper selection. Finally, 10 papers (10, [19][20][21][22][25][26][27][28][29] were selected. The results comprised 31 data sets, and the specific contents used in the study are listed in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that after the injection of exogenous T, both the ovulation and the embryo survival rates of sows improved (19,20). In contrast, Jimenez reported that although the ovulation rate of sows improved after T injection, the survival rate of embryos was reduced (21). In particular, the embryo survival rate of sows after DHT injection decreased significantly (21,22).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The mechanism whereby the ovary was apparently made more responsive to an ovulatory signal is not known. The hCG can be expected to increase production of follicular testosterone which, in turn, may increase circulating FSH concentrations [10]. Higher FSH levels in association with the increased LH activity from the hCG may be associated with the more rapid follicular growth and, presumably, follicular maturation.…”
Section: Discussionmentioning
confidence: 99%